Barriers to Energy Saving for Public Middle Schools in Bangkok: From School Management Perspective - Kiatruangkrai, Wuttipan; Leelarasmee, Ekachai (International Journal of Energy Economics and Policy, 2016)
The Government sector is one of the main energy consuming sectors in Thailand which consumed 2,064 GWh of total consumption in 2012. Due to Thailand need to import energy, so Government of Thailand announced to all government agencies to reduce energy consumption by 10%. Public school is one of government agencies, not only to reduce their consumption but also have responsibility to transfer knowledge and create the behavior of energy saving for students. However, it is not simple to fulfill this task due to many obstacles, called “Barriers”. The purpose of this paper is to identified the barriers which prevented public schools from energy saving and how to overcome those barriers, by interviewing with school managements as research method. The results highlight the government policies and values are the main barriers of energy saving in schools and also suggested various ideas of how to overcome those barriers in each level. Keywords: Energy saving, Barriers, public school JEL Classificationss: Q4, P28